(untitled) (Innovative Applications of AI, 2024)
The development of China’s economic construction and information technology has had a profound impact on the traditional manufacturing industry. In the transportation sector, the increasing demands for height, safety, speed, precise positioning, and stable operation have propelled the evolution of intelligent cranes. This paper focuses on the key characteristics of intelligent tower cranes and the development trends of remote control systems. It also explores the design and application of key technologies in the remote control systems of new types of intelligent cranes, further investigating the design theory and application techniques of their remote operating systems. This is aimed at better overcoming various challenges in future applications and fostering the innovative development of intelligent cranes.